Habitat-mediated effects of diurnal and seasonal migration strategies on juvenile salmon survival. (3rd September 2018) - Melnychuk, Michael C; Welch, David W
Abstract : Avoiding migration under daylight doubles salmon survival in risky habitats. Traveling only at night down clear rivers improves survival, presumably because juveniles are less visible to predators. Sunlight intensity matters less when migrating down silted rivers, likely because visual predation risk is low even in broad daylight. Salmon must balance nocturnal timing decisions with seasonal timing decisions about when to enter the ocean, and these behaviors are shaped by the habitats through which they migrate. Abstract: Behavioral decisions during periods of vulnerability to predation risk, such as migrations during the juvenile life-history stage, may strongly affect the probability of survival. Habitats through which animals migrate are heterogeneous, and risk-reducing behaviors may be more important in some habitats than others. Using biotelemetry data, diurnal and seasonal riverine migration patterns of >3800 juvenile salmon across 4 species, 12 watersheds, and 5 years were quantified to evaluate possible effects of migration timing on survival from lower river reaches to coastal waters. In small, clear rivers most salmon avoided migrating during daylight hours and average survival of fish migrating at night (55%; 95% confidence limits 50–61%) was twice that of fish migrating in daylight (24%; CL 17–31%). Conversely, in the large, heavily silted Fraser River neither preference for nocturnal travel nor effects of diurnal timing on survival were observed. Early ocean survival was also influenced by the timing of ocean entry, but in opposite directions for fish from the Fraser River and smaller rivers. In the Fraser River, average survival for later migrants (69%; CL 60–77%) was nearly twice that of earlier migrants (38%; CL 33–44%), likely related to seasonal increases in river flow. In contrast, in smaller rivers, average survival for earlier migrants (70%; CL 65–74%) was 3-fold greater than survival for later migrants (19%; 95% CL 14–25%). Together, these results demonstrate that timing decisions affecting survival of juvenile salmon during their migration are likely mediated by landscape characteristics that plausibly influence the risk of predation.